Optical bandgap control in Al2O3/TiO2 heterostructures by plasma enhanced atomic layer deposition: Toward quantizing structures and tailored binary oxides - Paul, Pallabi; Hafiz, Md. Golam; Schmitt, Paul; Patzig, Christian; Otto, Felix; Fritz, Torsten; Tuennermann, Andreas; Szeghalmi, Adriana (Spectrochimica Acta Part A-Molecular and Biomolecular Spectroscopy, 2021)
Atomically thin heterostructures and superlattices are promising candidates for various optoelectronic and photonic applications. Different combinations of Al2O3/TiO2 composites are obtained by plasma enhanced atomic layer deposition (PEALD). Their growth, composition, dispersion relation, and optical bandgap are systematically studied by means of UV/VIS spectrophotometry, spectroscopic ellipsometry (SE), x-ray reflectometry (XRR), scanning transmission electron microscopy (STEM) and x-ray photoelectron spectroscopy (XPS). Besides, an effective medium approximation (EMA) approach is applied to model the heterostructures theoretically. The refractive index and the indirect bandgap of the heterostructures depend on the ratio of the two oxides, while the bandgap is very sensitive to the thicknesses of the barrier and quantum well layers. A large blue shift of the absorption edge from 400 nm to 320 nm is obtained by changing the TiO2 (quantum well) thickness from 2 nm to 0.1 nm separated by 2 nm of Al2O3 (barrier) layers. PEALD unfolds the possibility of achieving optical quantizing effects within complex heterostructures enabling control of their structures down to atomic scale. It enables a path towards atomic scale processing of new ‘artificial’ materials with desired refractive indices and bandgap combinations by precise control of their compositions.
CRIS-Team Scopus Importer:2023-04-20
Keywords: Atomic layer deposition; Binary oxides; Dielectrics; Heterostructures; Quantum confinement; Superlattices